E and P Selectins as Potential Markers in the Assessment of the Severity of Acute Pancreatitis. Issue 4 (April 2018) - Tsaroucha, Alexandra K.; Schizas, Dimitrios; Vailas, Michail G.; Rachmani, Evangelia; Kanavidis, Prodromos; Asimakopoulos, Vyron; Vlachos, Sotirios; Sotiropoulou, Maria; Pitiakoudis, Michael S.; Simopoulos, Constantinos E.
Abstract : Objectives: Acute pancreatitis (AP) is commonly associated with the release of adhesion molecules such as E and P selectins. We designed the present study to evaluate the role of selectins as potential markers that could reflect the severity of the disease. Methods: One hundred fifty patients with AP constituted the patient group, whereas 70 healthy volunteers established the control group. In both groups, blood samples were taken for measurements of E selectin, P selectin, caspase-cleaved cytokeratin 18, and total soluble cytokeratin 18 levels on admission and days 1, 2, 4, and 6. Results: Values of E and P selectins on admission were both elevated compared with control subjects ( P < 0.01). The nonsurvivors had higher values of E selectin ( P < 0.04) and P selectin ( P < 0.03) on admission. Levels of E and P selectin showed positive correlation with the length of stay ( P < 0.05). E selectin on admission yielded a sensitivity of 75% and 78% specificity, whereas P selectin had a sensitivity of 67% and 91% specificity. Conclusions: Selectin values in the early course of AP may play a role as indicators of overall prognosis, which may help physicians in better understanding the pathophysiology of a benign disease that may have serious and detrimental complications.